Pivotal Role of the Basic Character of Organic and Salt Catalysts in C−N Bond Forming Reactions of Amines with CO2. Issue 3 (13th September 2019) - Hulla, Martin; Dyson, Paul J.
Abstract: Organocatalysts promote a range of C−N bond forming reactions of amines with CO2 . Herein, we review these reactions and attempt to identify the unifying features of the catalysts that allows them to promote a multitude of seemingly unrelated reactions. Analysis of the literature shows that these reactions predominantly proceed by carbamate salt formation in the form [BaseH][RR′NCOO]. The anion of the carbamate salt acts as a nucleophile in hydrosilane reductions of CO2, internal cyclization reactions or after dehydration as an electrophile in the synthesis of urea derivatives. The reactions are enhanced by polar aprotic solvents and can be either promoted or hindered by H‐bonding interactions. The predominant role of all types of organic and salt catalysts (including ionic liquids, ILs) is the stabilization of the carbamate salt, mostly by acting as a base. Catalytic enhancement depends on the combination of the amine, the base strength, the solvent, steric factors, ion pairing and H‐bonding. A linear relationship between the base strength and the reaction yield has been demonstrated with IL catalysts in the synthesis of formamides and quinazoline‐2, 4‐diones. The role of organocatalysts in the reactions indicates that all bases of sufficient strength should be able to catalyze the reactions. However, a physical limit to the extent of a purely base catalyzed reaction mechanism should exist, which needs to be identified, understood and overcome by synergistic or alternative methods. Abstract : Carbon dioxide activation by amines leads to a range of C−N bond forming reactions. Most types of organocatalysts promote the reactions predominantly by acting as bases that stabilize formation of carbamate salts in the form [BaseH][RR′NCOO]. Alternative mechanistic roles of organocatalysts in CO2 based reactions with amines are extremely rare.